STEEL SECTION HAVING THICKNESS OF AT LEAST 100 mm AND METHOD OF MANUFACTURING THE SAME

A steel section with a tailored chemical composition and manufacturing process addresses the challenges of high yield strength and weldability, achieving superior mechanical properties for large-scale construction.

JP2025004102AInactive Publication Date: 2025-01-14ARCELORMITTAL SA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024174082
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-12-18
Filing Date
2024-10-03
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for producing thick-walled steel sections with high yield strength and toughness face challenges such as overheating during low-temperature hot rolling and the negative impact of high alloying element additions on weldability.

Method used

A thick-walled steel section with a specific chemical composition and microstructure, including controlled amounts of carbon, manganese, silicon, copper, nickel, chromium, molybdenum, vanadium, nitrogen, aluminum, sulfur, phosphorus, niobium, and titanium, combined with a manufacturing process involving hot rolling and accelerated cooling to achieve high yield strength and weldability.

Benefits of technology

The solution results in steel sections with high yield strength, tensile strength, and excellent weldability, suitable for large-scale construction projects, reducing material costs and weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004102000007
    Figure 2025004102000007
  • Figure 2025004102000008
    Figure 2025004102000008
  • Figure 2025004102000001
    Figure 2025004102000001
Patent Text Reader

Abstract

To provide a steel heavy section having high tensile strength and excellent weldability.SOLUTION: A steel section includes a web central portion connected on each side to a flange portion having a thickness of at least 100 mm. The steel section contains, in weight percentage: 0.06-0.16% of C; 1.10-2.00% of Mn; 0.10-0.40% of Si; 0.001-0.50% of Cu; 0.001-0.30% of Ni; 0.001-0.50% of Cr; 0.001-0.20% of Mo; 0.06-0.12% of V; 0.0050%-0.0200% of N; 0.040% or less of Al; 0.040% or less of P; and 0.030% or less of S, and optionally contains at least one of less than 0.005% of Ti and 0.05% or less of Nb, with the remainder being impurities. A microstructure includes at least one vanadium precipitate that may include at least one metal selected from among chromium, manganese and iron. More than 70% of the precipitate has a mean diameter below 6 nm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention deals with a steel section with a central web connected on each side to flanges having a thickness of more than 100 mm. The steel section according to the invention is particularly well suited for the manufacture of columns for high-rise buildings, long spans and transfers, as well as belt trusses, outriggers and bridge girders. [Background technology]

[0002] The development of new modern structural steel grades is constantly driven by user demands for higher mechanical properties such as yield strength and toughness, as well as superior technical properties to ensure efficient manufacturing techniques in the workshop and on site. Summary of the Invention [Problem to be solved by the invention]

[0003] It is therefore an object of the present invention to provide a thick wall steel section which reaches a high yield strength of at least 485 MPa and a high tensile strength of at least 580 MPa and has good weldability.

[0004] In the practice of structural steel production, it is known that in order to improve strength and toughness, it is preferable to refine the structure through hot rolling at lower temperatures or to add some alloying elements for austenite grain refinement. Both solutions are not sufficient for heavy structural steel production, since overheating of the rolls is inevitable in the case of lower hot rolling temperatures. At the same time, the addition of high amounts of alloying elements reduces the weldability of the steel. [Means for solving the problem]

[0005] The object of the present invention is achieved by providing a thick-walled steel section according to claim 1. Moreover, this thick-walled steel section may have the characteristics according to claims 2 to 12. Another object is achieved by providing a method according to claim 13.

[0006] Other features and advantages of the present invention will become apparent from the following detailed description of the invention and the figures. [Brief description of the drawings]

[0007] [Figure 1] 1 is an electron micrograph showing irregularly distributed precipitates in the core of a flange of a thick section. [Diagram 2] 1 is an electron micrograph showing precipitates arranged in regularly spaced bands. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Unless otherwise specified, all composition percentages are given in weight percentage (wt%). With regard to the chemical composition of the steel, carbon plays an important role in forming the microstructure and achieving the targeted mechanical properties. Its main role is to strengthen the steel through the formation of carbides and / or carbonitrides of the metallic elements of the steel, as well as by quenching the martensite / bainite phase. The carbon content of the grades according to the invention is between 0.06 and 0.16 wt%. A carbon content below 0.06% does not provide a sufficient level of mechanical resistance, leading to yield strength values ​​below 485 MPa. On the contrary, a carbon content above 0.16% will result in a decrease in the ductility and weldability of the steel. The carbon content is preferably between 0.08 and 0.14% in order to obtain sufficient strength and weldability.

[0009] Manganese is an element that enhances hardenability. The manganese content of the grades according to the invention is between 1.10 and 2.00%. A manganese content below 1.10% does not result in a sufficient level of mechanical resistance. Conversely, a manganese content above 2.00% will result in a decrease in weldability or promote the formation of hard martensite-austenite constituents and will also have a negative effect on the toughness of the steel.

[0010] Silicon is a deoxidizing element and contributes to improving strength. A silicon content below 0.10% does not provide a sufficient level of mechanical resistance or good deoxidation. Conversely, a silicon content above 0.40% will result in the formation of oxides that will reduce the welding properties of the steel.

[0011] Copper is an element that contributes to improving the strength of steel by improving hardenability and precipitation strengthening. A copper content below 0.001% does not provide a sufficient level of mechanical resistance. On the other hand, a copper content above 0.50% will increase the carbon equivalent and thus impair the weldability of the steel during hot deformation caused by the penetration of Cu-rich phases into the grain boundaries or affect the hot brittleness.

[0012] Nickel is an element that contributes to improving the strength and toughness of steel. A nickel content of less than 0.001% does not provide a sufficient level of mechanical resistance. Conversely, a nickel content of more than 0.30% would lead to high alloying costs.

[0013] Chromium is an element that contributes to the strength of steel not only through solution hardening, but also through improved hardenability due to precipitation hardening. A chromium content below 0.001% does not provide a sufficient level of mechanical resistance. Conversely, a chromium content above 0.50% will result in the formation of coarse chromium carbides or chromium carbonitrides, which may degrade the toughness of the steel.

[0014] Molybdenum is an element that contributes to improving the strength of steel by improving its hardenability. If the molybdenum content is below 0.001%, it will not provide a sufficient level of mechanical resistance. On the other hand, a molybdenum content of more than 0.20% will reduce the toughness of the steel.

[0015] Vanadium is an important element used to achieve hardening and strengthening, not only by precipitation of nitrides, carbonitrides or carbides, but also through grain refinement. The formation of vanadium precipitates limits the coarsening of the austenite grains, resulting in a reduction in the ferrite grain size and an increase in strength due to precipitation in the ferrite phase. Vanadium also impedes the mobility of chromium and manganese in the cementite, which can be utilized for the formation of fine precipitates. A vanadium content below 0.06% does not provide a sufficient level of mechanical resistance. On the contrary, a vanadium content above 0.12% runs the risk of a reduction in toughness due to excessive precipitation, which must be avoided. In a preferred embodiment, the addition of vanadium is limited to 0.09% in order to further improve the toughness of the steel.

[0016] Nitrogen is an important element for forming nitrides and carbonitrides of metallic elements such as vanadium, niobium, aluminum and titanium. Their size, distribution density and stability have a significant effect on mechanical strengthening. Nitrogen contents below 0.0050% do not result in a sufficient level of precipitation and grain size control. To further improve these properties, a minimum concentration of 0.0060%, or even 0.0070%, or even better 0.0080% is preferred. On the contrary, nitrogen contents above 0.0200% result in the presence of free nitrogen in the steel, which is known to have a negative effect on toughness in the heat-affected zone after welding.

[0017] During hot rolling, part of the vanadium combines with nitrogen to form VN particles for anchoring the austenite grain boundaries. The remaining vanadium in solid solution subsequently precipitates in the form of fine precipitates during cooling of the steel, thus contributing significantly to the final strength. The inventors have found that precipitation strengthening can be enhanced by optimizing the vanadium to nitrogen ratio in the steel section to approach the stoichiometric ratio of 4:1. In a preferred embodiment, the V to N ratio is comprised between 2.5 and 7, and even between 3 and 5.

[0018] Aluminum can be added to steel for deoxidizing effect and to remove oxygen from the steel. If other deoxidizing elements are added to the steel, the aluminum content is 0.005% or less. Otherwise, the aluminum content is between 0.005% and 0.040%. If the aluminum content is too high, the formation of AlN takes precedence over VN, but since AlN is larger than VN, it is not as efficient at fixing the austenite grain boundaries as VN.

[0019] Sulfur and phosphorus are impurities that weaken grain boundaries and lead to the formation of central and microsegregations. Their contents should not exceed 0.030 and 0.040%, respectively, in order to maintain sufficient hot ductility and avoid deterioration of weldability.

[0020] Niobium is an element that may be optionally used to achieve hardening and strengthening by precipitation of nitrides, carbonitrides or carbides. Niobium inhibits the growth of austenite grains during rolling and refines them, thereby improving strength and low-temperature toughness. However, if its amount exceeds 0.05%, it may deteriorate the toughness of the heat-affected zone by hardening of martensite. On the other hand, if the amount of niobium is more than 0.05%, it fixes the available nitrogen, which prevents it from forming vanadium precipitates, ensuring the strengthening of the ductile core of the section.

[0021] Titanium is an element that may be optionally used to achieve hardening and strengthening by precipitation of nitrides, carbonitrides or carbides. However, if its amount is more than 0.005%, there is a risk of forming TiN instead of VN. Furthermore, TiN, being a cubic particle, may act as a stress concentrator and thus adversely affect the toughness and fatigue properties of the steel. In a preferred embodiment, the maximum amount of titanium is set at 0.003% or even 0.001%.

[0022] In a preferred embodiment, the carbon, manganese, chromium, molybdenum, vanadium, nickel and copper contents of such grades satisfy the following relationship: 0.4≦CEV≦0.6 CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15 is something that is fulfilled.

[0023] Adherence to these values ​​ensures that the hardenability of the steel section is in the correct range through sufficient formation of bainite while maintaining good weldability of the steel section. The reduced carbon equivalent allows to avoid welding processing steps such as preheating (if permitted) and also reduces manufacturing costs. In a preferred embodiment, CEV≦0.5%.

[0024] The steel section includes a central web portion connected on each side to flange portions.

[0025] The thickness of the flanges of the steel sections according to the invention is set to more than 100 mm, to allow the use of such beams especially in high-rise building structures, and is preferably less than 140 mm, since it is difficult to obtain a sufficient cooling rate to ensure the required tensile and toughness properties.

[0026] According to the invention, the webs and flanges of the thick section are composed of hardened zones resulting from water cooling of the surface and non-hardened zones in the core of the product. Each zone of the steel section may have a specific microstructure that may include one or more phases among tempered martensite, bainite, ferrite and pearlite. The ferrite may be present in the form of acicular ferrite or ordered ferrite.

[0027] The microstructure of each zone depends on the thickness of the steel section and the thermal path it is subjected to.

[0028] In a preferred embodiment, the microstructure of the flange portion comprises, from the surface to the core, a first zone comprising tempered martensite and possibly bainite, and a second zone comprising ferrite and pearlite.

[0029] The first region may, for example, extend up to 10 mm below the surface of the flange portion.

[0030] An essential feature of the present invention is the presence in the microstructure of the steel section of at least one vanadium precipitate, possibly containing one or more metals selected from chromium, manganese and iron. Such precipitates are selected from nitrides, carbides, carbonitrides or any combination thereof, and more than 70% and preferably more than 80% of such precipitates have an average diameter of less than 6 nm. The determination of the average diameter was carried out in the following way: the surface of each detected precipitate was measured and fitted to a corresponding circle, from which the diameter was derived, and the average diameter size of all detected precipitates was obtained.

[0031] In a preferred embodiment, the average density of the precipitates is mm 2 At least 500 precipitates per mm, preferably 2 These precipitates are known to have a beneficial effect on strength, which increases as the precipitate size decreases and the precipitate content increases.

[0032] Such precipitates are preferably present in the core area of ​​the flanges of the section, mainly in the ferrite phase. At least 70%, preferably at least 80%, of such precipitates have an average diameter of less than 6 nm. The reduction in the size of such precipitates increases their hardening effect and thus the tensile strength of the steel section.

[0033] In a preferred embodiment, two types of precipitates are present, preferably in the core area of ​​the flange of the steel section: - irregularly distributed precipitates within the ferrite, and - Precipitates arranged in regularly spaced bands and forming parallel sheets of closely packed grains.

[0034] The irregularly distributed precipitates are larger than those arranged in regularly spaced bands.

[0035] In a preferred embodiment, such regularly spaced precipitates contain at least vanadium and chromium.

[0036] In another preferred embodiment, more than 80% of the randomly distributed precipitates have an average diameter between 3.5 and 6 nm. Such precipitates preferably contain at least vanadium, chromium and iron.

[0037] The steel section according to the invention can be produced by any suitable manufacturing method, which the skilled person will be able to identify, but it is preferable to use a method which ends with accelerated cooling, and in that case with quenching and self-tempering of the surface area after the hot rolling step.

[0038] The method according to the invention comprises the following steps.

[0039] - providing a semi-finished product whose composition is according to the invention, - reheating said semi-finished product at a temperature above 1000°C and hot rolling it at a final rolling temperature of at least 900°C to obtain a hot rolled steel section, - cooling the hot-rolled steel section so as to cause quenching of martensite and / or bainite in the surface layer of all or part of the product, the unquenched part of the rolled product remaining at a temperature high enough to cause auto-tempering of the quenched surface layer of martensite and / or bainite and to convert austenite to ferrite and carbides in the core part of the section during subsequent cooling, the maximum temperature of the tempered surface of the product after quenching being 450-650°C, or even 550-650°C.

[0040] The steel sections of the invention are preferably produced by a process in which a semi-finished product made of the steel of the invention having the composition as defined above is cast and the cast input stock is heated to a temperature above 1000° C., preferably above 1050° C., more preferably above 1100° C. or above 1150° C., or used directly at such temperatures after casting without intermediate cooling, which allows complete dissolution of the vanadium carbonitride, which further participates in the precipitation strengthening mechanism.

[0041] The final hot rolling step is carried out at a temperature above 850° C. The finish rolling temperature is above 850° C. to ensure refinement of the austenite grains and thus the formation of a thinner microstructure after transformation, which is known to enhance toughness and strength properties.

[0042] During hot rolling, a combination of rolling steps and rolling temperature control is preferably used, the objective being to produce a fine structure through final recrystallization grain refinement during rolling.

[0043] The hot rolled product obtained by the above process is then cooled, preferably using a quenching and self-tempering process.

[0044] The so-called quenching and self-tempering treatment (QST) consists of cooling the hot-rolled steel section leaving the finishing stand of the rolling mill with a fluid so as to cause quenching of the martensite and / or bainite surface layer of all or part of the product. Moreover, at the exit of the fluid cooling zone, the unquenched part of the rolled product is at a temperature high enough to allow tempering of the martensite and / or bainite surface layer to take place during the subsequent air cooling.

[0045] The cooling liquid used to carry out the quenching and self-tempering steps is usually water with or without conventional additives or, for example, aqueous mineral salts. This liquid may be, for example, a mist obtained by suspending water in a gas, or it may be a gas, such as steam.

[0046] From a practical standpoint, the desired cooling of the rolled product depends on the cooling equipment used and on the proper selection of the length and flow characteristics of the cooling means.

[0047] The dimensions of the product are known, as is the composition of the steel and therefore its continuous cooling transformation diagram, which makes it possible to determine the conditions to be applied for the proper processing of the steel section, among which the temperature at which martensite is formed and the maximum time available to perform surface hardening to the desired depth.

[0048] Based on the curves of the temperature gradient in the core and skin of the rolled steel section, the amount of heat removed can be obtained as well as the characteristics of the cooling device and the flow rate of the fluid applied by the cooling device.

[0049] To monitor the formation of the desired microstructure in different zones of a steel section, the evolution of the skin temperature of the steel section starting from the end of the quenching of martensite and / or bainite has been measured. After quenching, the skin temperature increases, while the core temperature decreases continuously after the section leaves the last stand of the rolling mill. The skin and core temperatures at a given cross section converge towards a point where the two curves run substantially parallel to each other. The skin temperature at this point is called the "soaking temperature". EXAMPLES

[0050] The two grades, whose compositions are summarized in Table 1, were cast into semi-finished products and processed into steel sections according to the process parameters summarized in Table 2, which underwent heating, controlled hot rolling and subsequent water cooling to achieve quenching and self-tempering.

[0051] The compositions tested are summarized in the following table where the elemental contents are expressed as weight percent x 1000.

[0052] [Table 1]

[0053] Test 1 is a comparative example and test 2 is an example according to the invention.

[0054] The semi-finished steel products as cast products were processed under the following conditions.

[0055] [Table 2]

[0056] The obtained samples were then analyzed and the corresponding microstructural elements and mechanical properties were summarized in Tables 3 and 4, respectively.

[0057] The percentage of phases in the microstructure of the resulting steel sections was determined.

[0058] [Table 3]

[0059] The phase percentages in both zones, especially the core zone, of section n°1 are very similar to section n°2, indicating that the effect of vanadium precipitation strengthening is observed on a smaller microstructural scale.

[0060] Precipitation analysis performed by TEM examination of carbon extracted replicas taken from core areas in the thickness of the flanges of the sections showed the presence of vanadium precipitates. Fine precipitate analysis was performed by the TEM thin foil method, which allowed the quantification of the average size and density of the precipitates.

[0061] It was found that the precipitates responsible for the mechanical strengthening of the section are located in the core region of the steel section, specifically within the ferritic phase.

[0062] Figure 1 shows that the majority of vanadium precipitates have a spherical shape, whether large or small in size. The larger sized precipitates (typical size of about 6 nm in diameter) were mostly distributed irregularly. However, the fine precipitates (typical size of about 3 nm in diameter) were arranged in regularly spaced bands. From Figure 2 it can be seen that the microstructure consists of closely packed parallel sheets of vanadium particles. The sheets appear at regular intervals.

[0063] [Table 4]

[0064] [Table 5]

[0065] The mechanical properties of the tested steels were determined and are summarized in the following table.

[0066] [Table 6]

[0067] The examples show that the steel section according to the invention is unique in that it exhibits all of the targeted properties thanks to its particular composition and microstructure.

[0068] The steel sections according to the invention show excellent values ​​of high strength, toughness and good weldability, which to date cannot be easily achieved. The steel grade according to the invention allows design and construction teams involved in large scale building projects to benefit from more efficient structural solutions. The higher yield strength of the steel sections allows for weight reduction and lower transportation and manufacturing costs than other commonly used structural steel grades. The invention therefore represents a tremendous contribution to the construction industry.

Claims

1. A steel section having a central web connected to flanges having a thickness of at least 100 mm on each side, said steel section being in weight percent C: 0.06-0.16% Mn: 1.10-2.00% Si: 0.10-0.40% Cu: 0.001-0.50% Ni: 0.001-0.30% Cr: 0.001~0.50% Mo: 0.001-0.20% V: 0.06-0.12% N: 0.0050% to 0.0200% Al≦0.040% P≦0.040% S≦0.030% and optionally containing, in weight percentages, one or more of the following elements: Ti<0.005% Nb≦0.05% 1. A steel section comprising: a steel section including at least one vanadium precipitate which may also include one or more metals selected from chromium, manganese and iron, the balance being iron and refinement-derived impurities, the microstructure of the steel section including at least one vanadium precipitate which may also include one or more metals selected from chromium, manganese and iron, the precipitates being selected from nitrides, carbides, carbonitrides or any combination thereof, and more than 70% of such precipitates having an average diameter of less than 6 nm.

2. The composition of such sections is as follows: 0.4≦CEV≦0.6 Here, CEV=C+Mn / 6+(Cr+Mo+V) / 5+(Ni+Cu) / 15 2. The steel section of claim 1 , wherein:

3. 3. The steel section according to claim 1 or 2, wherein the ratio of the amount of vanadium to the amount of nitrogen is between 2.5 and 7.

4. 4. A steel section according to any one of claims 1 to 3, wherein the microstructure of said flange portion comprises, from the surface to the core, a hardened zone comprising tempered martensite and which may comprise bainite, and a core zone comprising ferrite and pearlite.

5. Such a steel section is mm 2 The steel section of any one of claims 1 to 4, comprising a portion having an average density of at least 500 precipitates per square inch.

6. A steel section according to any one of the preceding claims, wherein at least a portion of such precipitates are arranged in regularly spaced bands.

7. 7. The steel section of claim 6, wherein more than 80% of such regularly spaced precipitates have an average diameter of less than 3 nm.

8. 8. A steel section according to claim 6 or 7, wherein said regularly spaced precipitates contain at least vanadium and chromium.

9. A steel section according to any one of claims 4 to 8, wherein at least a portion of such precipitates are randomly distributed in the ferritic phase located in the core of the steel section.

10. The steel section according to claim 9, wherein more than 80% of said randomly distributed precipitates have an average diameter between 3.5 and 6 nm.

11. The steel section of claim 10 , wherein said irregularly distributed precipitates comprise at least vanadium, chromium and iron.

12. The steel section according to any one of the preceding claims, wherein the precipitates are located in the core region.

13. The steel section according to any one of the preceding claims, wherein the flange portion has a thickness of up to 140mm.

14. The following steps: - providing a semi-finished product whose composition is according to any one of claims 1 to 3, - reheating said semi-finished product at a temperature above 1000°C and hot rolling it at a final rolling temperature of at least 850°C to obtain a hot-rolled steel section, - cooling the hot-rolled steel section so as to cause a quenching of the martensite and / or bainite of the surface layer of all or part of the product, the unquenched part of the rolled product remaining at a temperature high enough to cause auto-tempering of the quenched surface layer of martensite and / or bainite and to convert austenite to ferrite and carbides in the core of the section during subsequent cooling, the maximum temperature of the tempered surface of the product after quenching being between 450 and 650°C, A method for manufacturing a steel section comprising:

Citation Information

Patent Citations

  • Manufacture of rolled shape steel excellent in toughness

    JP1993132716A

  • Extremely thick wide flange shape having high strength and high toughness

    JP1999323477A

  • Method for producing steel material for structural use excellent in earthquake-proof characteristic

    JP2004232091A

  • Low yield ratio wide flange beam having excellent earthquake resistance and its production method

    JP2005264208A

  • High-strength hot-rolled steel sheet having both formability and fatigue characteristic in base material and weld heat affected zone

    JP2013040380A